Some empirical tests on the integration of economic activity between the Euro area and the accession countries - Iikka Korhonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
This note looks at the correlation of short-term business cycles in the euro area and the EU accession countries.The issue is assessed with the help of vector autoregressive models.There are clear differences in the degree of correlation between accession countries.For Hungary and Slovenia, euro area shocks can explain a large share of variation in industrial production, while for some countries this influence is much smaller.For the latter countries, the results imply that joining the monetary union could entail reasonably large costs, unless their business cycles converge closer to the euro area cycle.Generally, for smaller countries the relative influence of the euro area business cycle is larger.Also, it is found that the most advanced accession countries are at least as integrated with the euro area business cycle as some small present member countries of the monetary union.
URN:NBN:fi:bof-201408072189
Keywords: E32; F15; F42; 330; optimal currency area; monetary union; EU enlargement